Co-administration of Spondias mombin and Metformin mitigates Streptozotocin-induced hepatorenal injury - Bala Peter Akwu; Adeshina John Ajibade; Ayodeji Zabdiel Abijo; Testimony Priscilla Ajibade; David Busuyi Kehinde; Jacob Adewale Siyanbade; Sunday Aderemi Adelakun; Olusola Atilade Adeeyo (Elsevier, 2022)
Background: As a result of its many therapeutic properties, including its potent anti-hyperglycemic effect, the Spondias mombin plant is quickly gaining popularity as a local therapeutic agent for the treatment of many ailments. This work aimed at investigating the effects of co-administration of Spondias mombin and metformin in STZ-induced hyperglycemia and hepatorenal injury in the Wistar rat model, specifically focusing on the morphological, biochemical, and immunohistochemical alterations in the liver and kidney. Methods: Hundred healthy adult male Wistar rats weighing (80-150g) and assigned into 10 groups (A-J) (n= 10 each). The normal control group A received a single dose of citrate buffer (1mL/kg, p.o) while groups B, C, D, E, F, and I were induced with hyperglycemia by administering a single dose of Streptozotocin (60 mg/kg, i.p). Group B was left untreated while others were treated with Spondias mombin (600 mg/kg p.o), (400 mg/kg p.o), (200 mg/kg p.o), metformin (12.5 mg/kg p.o), and Spondias mombin + metformin (12.5 mg/kg) respectively. Groups G and H were administered Spondias mombin only (400 mg/kg) and metformin (12.5 mg/kg) respectively; and group J was not induced but administered both Spondias mombin only (400 mg/kg) and metformin (12.5 mg/kg). Administration in all groups lasted for 28 days. Rats were sacrificed and the liver and renal tissues were excised for histopathological examination using the H&E stain, while the Periodic acid Schiff reagent, and Masson Trichome stains were employed for connective tissue assessments. Oxidative stress parameters (CAT, SOD, GSH, and MDA) were evaluated. The assessment of liver enzymes (ALT, AST, and ALP) and renal markers (Urea, and Creatinine) were also carried out. Kidney and liver Bcl-2 expressions were assessed immunohistochemically. The data obtained were analyzed by ANOVA and Duncan Multiple Range post hoc test and presented as mean ± SEM at p <0.05. Results: Following STZ induction, there were histopathological alterations in the renal and liver tissues while Spondias mombin treatment and combined Spondias mombin treatments with metformin mitigated these alterations. Anti-oxidant enzyme markers; CAT, SOD activities, and GSH level significantly decreased (p<0.05) while MDA increased significantly. Markers of liver injury; AST, ALT, and ALP were significantly increased (p < 0.05) in the STZ-only group while Spondias mombin treatment and combined Spondias mombin and metformin restored these changes. In the same manner, serum urea and creatine levels were significantly increased (p < 0.05) while Spondias mombin treatment and combined Spondias mombin and metformin ameliorated this. Immunohistochemical observations showed upregulated expressions of Bcl-2 in the liver rather than the kidney Conclusions: Based on the findings from this research is the phytomedicinal drug potential of Spondias mombin viz-a-viz MTF and the establishment of the combined actions of Spondias mombin and MTF . Co-administration of Spondias mombin and metformin mitigated Streptozotocin-induced hepatorenal histopathological alterations via anti-hyperglycaemic, anti-oxidative and anti-apoptotic potentials in the liver.